Livelihood benefits and costs from an invasive alien tree (Acacia dealbata) to rural communities in the Eastern Cape, South Africa. (1st January 2019) - Ngorima, A.; Shackleton, C.M.
Abstract: The negative effects of invasive alien species (IAS) are increasingly invoked to justify widespread and usually top-down approaches for their management or eradication. However, very little of the research or discourse is based on investigating local perceptions, uses and struggles with IAS, and how their presence influences and changes local livelihoods. The objective of this study was to assess the perceptions and livelihood uses of Acacia dealbata by local communities at three localities in the montane grasslands of the Eastern Cape, South Africa, using a combination of random household interviews, focus group discussions and participatory tools. We calculated direct-use values for each product and household (based on quantity used and local prices) and disaggregated these by gender of the household head and wealth quartiles. The results revealed the dualistic role of A. dealbata in local livelihoods. On the one hand, A. dealbata was widely used for firewood (100% of households), tools (77%) and construction timber (73%), with limited use for traditional medicines and forage. The cumulative value of approximately ZAR 2870 (±US$224) per household per year (across all households) represents considerable cash saving to households, most of whom are quite poor by national and international measures. On the other hand, the increasing extent of A. dealbata (93% said it was increasing) exacerbates local household vulnerability though reported reductions in cultivated areas, crop yields and forage production, and allegedly higher risks of crime. This quandary is well encapsulated by the considerable majority of respondents (84%) not wanting higher extents and densities of A. dealbata, but an equally high majority not wanting its total removal from local landscapes. Most respondents disliked A. dealbata in fields, close to homesteads or along primary access routes, and were more tolerant of it away from such sites. Institutional and use dynamics have varied over several decades in response to the changing extent and densities of A. dealbata and the broader political and socio-economic contexts. These results indicate that greater efforts are required to understand perceptions and uses of IAS by the people who live with them, and to direct such understanding into more spatially and temporally contextualised response strategies where required. Highlights: Benefits and costs from invasive Acacia dealbata were assessed for three sites. A. dealbata was widely used for firewood, tools and timber. Annual direct-use value of ZAR 2870 per household provided major cash savings. Costs were lost arable production, cover for criminals and roots damaging buildings. The trade-offs been benefits and costs were spatially and socially variable.